2009
DOI: 10.1021/la901784k
|View full text |Cite
|
Sign up to set email alerts
|

The Isotropic−Nematic Interface in Suspensions of Na−Fluorohectorite Synthetic Clay

Abstract: Colloidal suspensions of Na-fluorohectorite synthetic clay platelets in saline water exhibit coexisting isotropic and nematic phases, due to gravitational separation of the polydisperse particles. We study the ordering of the platelets at the interfaces between various coexisting phases. Four different experimental techniques are employed: visual observation of birefringence, synchrotron wide angle and small-angle X-ray scattering, and magnetic resonance imaging. We find that at the narrow isotropic sol-nemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 50 publications
1
47
0
Order By: Relevance
“…11,12,[39][40][41] Surprisingly, the IN coexistence for platelets is only weakly dependent on size polydispersity. 37 For these reasons, a relatively large amount of effort has been devoted to locating the isotropic-nematic coexistence for OHSC in the present paper by employing three different methods: (i) event-driven MD simulations, (ii) histogram method to determine the probability distribution of the nematic order parameter S 2 , and (iii) direct NPT MC simulations.…”
Section: B Isotropic-nematic Coexistencementioning
confidence: 98%
“…11,12,[39][40][41] Surprisingly, the IN coexistence for platelets is only weakly dependent on size polydispersity. 37 For these reasons, a relatively large amount of effort has been devoted to locating the isotropic-nematic coexistence for OHSC in the present paper by employing three different methods: (i) event-driven MD simulations, (ii) histogram method to determine the probability distribution of the nematic order parameter S 2 , and (iii) direct NPT MC simulations.…”
Section: B Isotropic-nematic Coexistencementioning
confidence: 98%
“…Free rotation of clay platelets is hampered owing to large hydrodynamic radii and excluded volumes are generated between the platelets [ 33 ] resulting in liquid-crystalline ordering and birefringence. [ 34 ] In the same line, continuously increasing concentrations of suspensions by evaporation forces alignment of platelets. As might be anticipated, the degree of alignment is, however, strongly ( Figure 2D ).…”
mentioning
confidence: 93%
“…However, research in the past decade has revealed the existence of nematic phases for selected natural and synthetic clays [8][9][10], whose I-N transition occurred at concentration lower than the sol-gel transition point that is strongly dependent on the ionic strength of the solvent. To date, there seems to be little work showing the ionic strength controlled phase diagrams of charged, discotic suspensions that display both gel phase and stable liquid crystal phases.…”
Section: /15mentioning
confidence: 99%